Influencing factors for medication adherence among inpatients with chronic diseases based on latent profile analysis - WANG Xiaoshan, YE Lixiang, CHEN Li, LI Minxiang, WANG Xinyu, CAI Xiaoxia (预防医学)
Objective: To explore the types of medication adherence and their influencing factors among inpatients with chronic diseases based on latent profile analysis, so as to provide the basis for improving medication adherence among patients with chronic diseases. Methods: The inpatients with chronic diseases admitted to the Second Affiliated Hospital of Hainan Medical University were selected as the study subjects. Demographic information, chronic disease status, and health education were collected through questionnaire surveys. Medication adherence was assessed using the Medication Adherence Scale and categorized based on the scores of its eight items through latent profile analysis. Factors affecting medication adherence among inpatients with chronic diseases were analyzed using a multinomial logistic regression model. Results: Totally 290 valid questionnaires were recovered, with an effective recovery rate of 97.64%. There were 157 males (54.14%) and 133 females (45.86%), with a median age of 61 (interquartile range, 21) years. The median score of medication adherence was 4.75 (interquartile range, 4.50). Based on latent profile analysis, medication adherence was categorized into three types: subjective neglect with poor adherence (38.97%), subjective confidence with fluctuating adherence (28.28%), and self-reflective with good adherence (32.76%). Multinomial logistic regression analysis showed that compared to the subjective confidence with fluctuating adherence, family monthly income (5 000-10 000 yuan, OR=2.981, 95%CI: 1.055-8.429), comorbidity of chronic diseases (OR=3.478, 95%CI: 1.579-7.661), number of health education sessions received in the past year (≤1 session, OR=0.329, 95%CI: 0.120-0.907; 2 sessions, OR=0.363, 95%CI: 0.138-0.950), and health information literacy scores (<60 points, OR=2.596, 95%CI: 1.209-5.573) were statistically associated with subjective neglect with poor adherence (all P<0.05). Conclusion: Subjective neglect with poor medication adherence among inpatients with chronic diseases is associated with family monthly income, comorbidity of chronic diseases, the number of health education sessions received, and health information literacy.